1996
DOI: 10.1152/jn.1996.76.5.3059
|View full text |Cite
|
Sign up to set email alerts
|

Metabotropic glutamate receptor agonist-induced hyperpolarizations in rat basolateral amygdala neurons: receptor characterization and ion channels

Abstract: 1. Metabotropic glutamate receptor (mGluR)-agonist-induced hyperpolarizations and corresponding outward currents were analyzed in basolateral amygdala (BLA) neurons in rat brain slice preparations with current-clamp and single-electrode voltage-clamp recording to characterize the mGluR subtype(s) and the ion channel(s) mediating this response. 2. The mGluR agonist (1S,3R)-1-amino-cyclopentane-1,3-dicarboxylic acid (1S,3R-ACPD) induced a membrane hyperpolarization or outward current in BLA neurons in a concentr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
28
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 0 publications
7
28
1
Order By: Relevance
“…The multiple responses to IS,3R-ACPD agree with previous reports from this laboratory (Rainnie et al 1994;Holmes et al 1996a, b) IS,3R-ACPD (50 FM) produced an inward current with a mean peak amplitude of 26 + 13 pA (n = 9) in the absence, and 31 + 14 pA (n = 8) in the presence of D-APV, CNQX and TTX; similarly, 1S,3R-ACPD (100 #M) induced currents of 43 + 9 (n = 16) and 35 + 12 pA (n = 13) in the absence and presence of D-APV, CNQX and TTX, respectively. All subsequent experiments were conducted in the constant presence of these antagonists.…”
Section: Tissue Preparationsupporting
confidence: 90%
See 1 more Smart Citation
“…The multiple responses to IS,3R-ACPD agree with previous reports from this laboratory (Rainnie et al 1994;Holmes et al 1996a, b) IS,3R-ACPD (50 FM) produced an inward current with a mean peak amplitude of 26 + 13 pA (n = 9) in the absence, and 31 + 14 pA (n = 8) in the presence of D-APV, CNQX and TTX; similarly, 1S,3R-ACPD (100 #M) induced currents of 43 + 9 (n = 16) and 35 + 12 pA (n = 13) in the absence and presence of D-APV, CNQX and TTX, respectively. All subsequent experiments were conducted in the constant presence of these antagonists.…”
Section: Tissue Preparationsupporting
confidence: 90%
“…This laboratory has previously reported that, in neurones of the basolateral amygdala, the mGlu agonists trans-and 1S,3R-ACPD predominantly evoke an outward current that is typically followed by inward current (Rainnie et al 1994). It was further shown that the outward current is mediated through a group II-like mGlu coupled to large conductance (BK) calcium-dependent potassium channels (Holmes, Keele, Arvanov & Shinnick-Gallagher, 1996a). The mechanism underlying the inward current is unknown, but it is increased in amplitude following amygdala kindling-induced epileptogenesis (Holmes, Keele & Shinnick-Gallagher, 1996b).…”
mentioning
confidence: 99%
“…Similar to other group III mGluRs (Saugstad et al, 1996(Saugstad et al, , 1997Corti et al, 1998), mGluR4 receptors positively couple to inwardly rectifying K ϩ channels in amphibian oocytes (Sharon et al, 1997). L-AP-4 can also activate K ϩ channels in CNS neurons (Holmes et al, 1996;Dutar et al, 1999). Through this mechanism, activation of mGluR4 might affect neuronal sensitivity to excitotoxic damage independently of changes in glutamate release.…”
Section: Discussionmentioning
confidence: 94%
“…Application of 1S, 3R-ACPD at concentrations of 1 mM resulted in membrane hyperpolarization in DUM neurons. Hyperpolarizing responses produced by activation of postsynaptic mGluRs with 1S, 3R-ACPD also have been shown in neurons of the rat basolateral amygdala (Rainnie et al ., 1994;Holmes et al ., 1996). They suggested from their studies that the hyperpolarization is G-proteine mediated and results from activation of a TEA-sensitive, calcium-dependent potassium conductance.…”
Section: Discussionmentioning
confidence: 99%